Efavirenz pharmacogenetics and metabolic toxicity in black South Africans - Makgai, Lesiba Meshack (Department of Medicine, 2023)
Background: Efavirenz is associated with hepatotoxicity, dyslipidaemia and dysglycaemia. We aimed to determine if CYP2B6 composite metaboliser genotypes influence lipids, glucose and ALT concentrations. Methods: Data and DNA from South African antiretroviral therapy (ART)-naïve participants initiating efavirenz with emtricitabine plus tenofovir disoproxil fumarate (TDF) were used to characterise associations between CYP2B6 metaboliser genotypes and the percentage difference in metabolic parameters from baseline to week 48 using univariate and multivariate linear regression models. Results: A total of 171 participants were successfully genotyped. Median baseline age was 32 years, CD4 count was 292 cells/mm3 and log10 viral load was 4.42 copies/ml. Univariate analyses showed significant associations between CYP2B6 slow metaboliser genotype and total cholesterol (β = 13.78, p = 0.003), LDL cholesterol (β = 15.89, p = 0.008) and HDL cholesterol (β = 24.78, p = 0.002). These associations remained significant in multivariate analyses adjusting for age, sex, weight, baseline CD4 cell count and viral load [total cholesterol (β = 14.93, p< 0.001), LDL cholesterol (β = 15.57, p = 0.014), and HDL cholesterol (β = 24.22, p< 0.001)]. No associations were found between CYP2B6 metaboliser genotype and triglycerides, glucose or ALT. Conclusion: Among Black South African participants on efavirenz-based ART, CYP2B6 slow metaboliser genotype was associated with high cholesterol concentrations. In an African population with high prevalence of CYP2B6 slow metabolisers, close monitoring of lipids is needed.